Factors increasing the risk for food addiction in Ecuadorian students - Reivan Ortiz, Geovanny Genaro; Campoverde, Ximena; Vinañzaca, Juan; Estrada, Johanna; Yanza, Rafael; Granero, Roser (Frontiers in Psychiatry, 2024)
Background Food addiction (FA) is a construct that has gained interest in recent years, but its relevance in the Ecuadorian population has not yet been explored. The aims of this study were to explore the differences in the psychological profile (including FA) between university students from Ecuador and to identify the underlying structure of the relationships of the FA severity level through a mediational model. Methods The sample consisted of 972 university students, women and men (mean age: 20.1 years old, SD = 2.6), recruited from four Ecuadorian regions. The assessment tools included a unidimensional scale of FA, eating-related measures, emotion regulation state, impulsivity, and psychopathology state. Path analysis modeled the direct and indirect effects explaining the FA severity level. Results The results indicated that higher psychopathological levels were associated with FA. Similarly, no differences in FA were observed between the Ecuadorian regions. The path analysis suggested that older age, female sex, and higher difficulties in emotional regulation, impulsivity, negative mood, and anxiety trigger disordered eating; subsequently, more impaired eating behavior impacted the FA level. Conclusion FA is a complex clinical entity that includes multiple components related to eating disorders (EDs) and other mental health problems. The results of this study provide empirical knowledge for designing evidence-based prevention and treatment strategies.